Atypical presentation of sweat dermatitis with review of literature - Rohini Soni; Archana J Lokhande; Paschal D'souza (Wolters Kluwer Medknow Publications, 2019)
Sweat dermatitis is a peculiar kind of irritant inflammatory dermatoses occurring due to prolonged exposure of retained sweat over the skin. It is commonly seen in hot and dry climates like tropics during summer months due to thermal stress. Typically, parchment paper or cellophane paper like scaling is seen over occluded areas of back, shoulder, and other areas. Here we have reported a varied presentation of sweat dermatitis in the form of its coexistence with miliaria rubra (impending to thermal burn). Further we have also observed co existing pityriasis versicolor and sweat dermatitis where the former has prevented the development of latter. Till date there is very little discussion on this condition, so we have tried to provide a concise review about sweat dermatitis along with its classical to atypical presentation with special emphasis on dermoscopy.